1996
DOI: 10.1159/000244284
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Cyclooxygenase Inhibitor Ibuprofen on Retinal and Choroidal Blood Flow during Hyperoxia in Newborn Piglets

Abstract: Purpose: The effect of the cyclooxygenase inhibitor ibuprofen (IB) on choroidal (ChBF) and retinal (RBF) blood flow during hyperoxia was examined in 21 spontaneously breathing newborn piglets. Methods: ChBF and RBF were measured using radiolabelled microspheres before and 30 min after either saline or IB (30 mg/kg, IV) infusion in room air and subsequently, after 90 min of hyperoxia (O2). Results: The basal RBF and ChBF did not change after IB infusion. However, during hyperoxia a significant decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
2
2
1
Order By: Relevance
“…The present results indicating a substantial involvement of thromboxane differ from the conclusion advanced in a recent study by Stiris et al (1996), wherein the cyclooxygenase inhibitor ibuprofen did not affect the status of RBF in the piglet after 90 min of sustained hyperoxia. Although piglets were studied in each instance, the respective drugs chosen for thromboxane inhibition represent important differences between these studies.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The present results indicating a substantial involvement of thromboxane differ from the conclusion advanced in a recent study by Stiris et al (1996), wherein the cyclooxygenase inhibitor ibuprofen did not affect the status of RBF in the piglet after 90 min of sustained hyperoxia. Although piglets were studied in each instance, the respective drugs chosen for thromboxane inhibition represent important differences between these studies.…”
Section: Discussioncontrasting
confidence: 99%
“…In our model, calculated RBF decreased 42 % during the initial 20 min of 100 % oxygen breathing. The magnitude of this response was similar to that measured in piglets with microspheres by Hardy et al (1996) (44 %) and Stiris et al (1996) (32 %) after 45 and 90 min of sustained hyperoxia, respectively. The mechanistic basis for this retinal response to elevated PaO # has yet to be systematically clarified.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This difference apparently depended on whether or not the animals were paralysed with pancuronium. Inasmuch as ibuprofen did not alter cardiac output in previous studies (22), we think that the increase in cardiac output observed in the ibuprofen-treated animals in this study is a confounder and did not influence the results. We do not think that increased cardiac output explains the increase in CBF and DCBV in response to CO 2 changes because the slight increase in cardiac output probably produced the slight increase in arterial blood pressure observed in the ibuprofen-treated animals.…”
Section: Discussionsupporting
confidence: 45%
“…We did not measure cerebral prostanoids in this experiment, but data previously obtained in our laboratory (22) have shown a significant and sustained reduction of prostanoid synthesis in vitreous 120 min after ibuprofen administration.…”
Section: Discussionmentioning
confidence: 99%